2020
DOI: 10.21203/rs.3.rs-81150/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Can physical activity protect against depression and anxiety during the COVID-19 pandemic? A rapid systematic review

Abstract: The Covid-19 pandemic is affecting the entire world population. During the first spread, most governments have implemented quarantine and strict social distancing procedures. Similar measures during recent pandemics resulted in an increase in post-traumatic stress, anxiety and depression symptoms. The development of novel interventions to mitigate the mental health burden are of outmost importance. In this rapid review, we aimed to provide a systematic overview of the literature with regard to associations bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 45 publications
2
14
0
Order By: Relevance
“…The purpose of the current study was to examine associations between physical activity, mental health, and mental illness during the COVID-19 pandemic. In line with emerging literature (47), individuals who maintained their levels of physical activity demonstrated less psychological disturbance. Results indicate a positive association between changes in MVPA and mental health, where those who experienced the greatest decline in MVPA reported relatively greater psychological distress and lower life satisfaction.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The purpose of the current study was to examine associations between physical activity, mental health, and mental illness during the COVID-19 pandemic. In line with emerging literature (47), individuals who maintained their levels of physical activity demonstrated less psychological disturbance. Results indicate a positive association between changes in MVPA and mental health, where those who experienced the greatest decline in MVPA reported relatively greater psychological distress and lower life satisfaction.…”
Section: Discussionsupporting
confidence: 77%
“…A significant body of research conducted prior to COVID indicates a positive relationship between mental health and physical activity (6,7,13). The results of the current study and the greater literature (47,48) suggest that such associations hold true during a period of pandemic and significant socioeconomic disruption. Indeed, given both the extent and severity of disruptions, it is remarkable that a significant proportion of depressive symptomatology -7.7% of variance accounted forwas associated with MVPA.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Indeed, our sample in fact is somewhat skewed towards limited musical training (see supplemental Figure 20), yet music-related activities were most frequently indicated as the top choice for coping with the pandemic-related psychological distress. Recent studies have highlighted the role of physical exercise [40][41][42] and other leisure activities such as reading, making handcrafts, talking with friends and watching TV or film 7,43,44 as protective factors against developing psychological distress symptoms associated with the COVID-19 pandemic. To the best of our knowledge, however, none of these studies investigated the role of music in coping with COVID-19-related adversities and mitigating their effects within the context of other activities or across multiple countries (see 45 for an exception, limited however to a highly educated sample of 400 individuals).…”
Section: Discussionmentioning
confidence: 99%
“…In regard to the preventive measures required to be adopted concerning the mental health of students, a rapid systematic review demonstrated the protective effect of a routine of physical activity during the COVID-19 period. Maintaining physical fitness has also been demonstrated to reduce the risk of developing symptoms of depression by 12%-32% and the risk of experiencing anxiety by 15%-34% in the general population [41]. Therefore, during forced isolation, such as the one during the pandemic crisis, certain authors have suggested studying the role of online exercise programs, such as the #StayHomeStayFit project by the University of Milan [42], in promoting fitness and preventing mental health disorders [41].…”
Section: Covid-19 Context Of School Closuresmentioning
confidence: 99%